2017
DOI: 10.1186/s12891-017-1559-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical shoulder angle combined with age predict five shoulder pathologies: a retrospective analysis of 1000 cases

Abstract: BackgroundAcromial morphology has previously been defined as a risk factor for some shoulder pathologies. Yet, study results are inconclusive and not all major shoulder diseases have been sufficiently investigated. Thus, the aim of the present study was to analyze predictive value of three radiological parameters including the critical shoulder angle, acromion index, and lateral acromion angle in relationship to symptomatic patients with either cuff tear arthropathy, glenohumeral osteoarthritis, rotator cuff t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 15 publications
6
68
2
3
Order By: Relevance
“…There is a great interest to change the radiological CSA towards to “normal” values and thereby reducing an overload of the rotator cuff. Although it has not yet been clarified which sub‐component (glenoid inclination, lateral acromial roof extension, acromial height) has the greatest impact, arthroscopic lateral acromioplasty is already performed . Our data could support lateral acromioplasty.…”
Section: Discussionmentioning
confidence: 60%
“…There is a great interest to change the radiological CSA towards to “normal” values and thereby reducing an overload of the rotator cuff. Although it has not yet been clarified which sub‐component (glenoid inclination, lateral acromial roof extension, acromial height) has the greatest impact, arthroscopic lateral acromioplasty is already performed . Our data could support lateral acromioplasty.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, smaller CSAs produce a resulting vector force of the deltoid that is unbalanced against the glenoid and thus, increasing the risk for the development of concentric osteoarthritis 8 29. Though our findings suggest that the CSA can be associated with other pathologies such as impingement27 and is not associated with glenoid erosion after hemiarthroplasty,36 further research is warranted to ascertain these results and to determine the mechanism through which they develop.…”
Section: Discussionmentioning
confidence: 72%
“…Three studies (n=323) found that those with osteoarthritis had a significantly lower CSA (p<0.05) 14 28 29. One study (n=500) reported a trend towards significance (OR=0.87 (95% CI 0.75 to 1.01); p=0.06) for the same association 27. One study (n=298) determined that of the patients with a CSA <30°, 93% had osteoarthritis 8.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations